2013
DOI: 10.1016/j.schres.2013.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptor 5 binding and protein expression in schizophrenia and following antipsychotic drug treatment

Abstract: Metabotropic glutamate receptor 5 (mGluR5) has been identified as a potential therapeutic target for schizophrenia, primarily due to its ability to indirectly modulate glutamatergic signalling through the NMDA receptor (NMDAR). Despite its potential, molecular studies characterising mGluR5 in schizophrenia are limited. We therefore aimed to determine if the mGluR5 binding site or protein levels were altered in schizophrenia or by current antipsychotics. Using in-situ radioligand binding and immunoblot, we meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 44 publications
3
31
3
Order By: Relevance
“…There was no effect of gender or hemisphere on mGluR5 mRNA expression. We have previously reported no change in mGluR5 monomer levels in this cohort in DLPFC [17]. However, mGluR5 dimer expression was 53.5% higher in schizophrenia subjects compared to controls (F 1,70 =8.688, p<0.001; co-varying for freezer storage time, which correlated with dimer levels [ Table S2]: F 1,69 =44.808, p<0.001).…”
Section: Detection Of Mrna and Proteinsmentioning
confidence: 60%
See 3 more Smart Citations
“…There was no effect of gender or hemisphere on mGluR5 mRNA expression. We have previously reported no change in mGluR5 monomer levels in this cohort in DLPFC [17]. However, mGluR5 dimer expression was 53.5% higher in schizophrenia subjects compared to controls (F 1,70 =8.688, p<0.001; co-varying for freezer storage time, which correlated with dimer levels [ Table S2]: F 1,69 =44.808, p<0.001).…”
Section: Detection Of Mrna and Proteinsmentioning
confidence: 60%
“…After one week of acclimatization, rats were distributed into 9 treatment groups (3 treatments x 3 treatment-durations; n=6/group), as described previously [17]. Animals were fed prepared food pellets 3 times/day at 8 hour intervals, containing either: (1) typical antipsychotic, haloperidol (0.1mg/kg body weight; daily total 0.3mg/kg), (2) atypical antipsychotic, olanzapine (1mg/kg body weight; daily total 3mg/kg), (3) vehicle control (empty food pellets), for short term (8 days), medium term (15 days) and long term (35 days) durations.…”
Section: Animal Housing and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important that the drug dosages used in this study have been used previously and have been shown to be pharmacologically and behaviourally effective (Assié et al, 2006;Deng et al, 2007;Han et al, 2009a;WestonGreen et al, 2011). It should also be noted that female rats were used in this study, because our previous studies have shown that female rats are a suitable model for investigating pharmacological effects of antipsychotics (Han et al, 2009a;Han et al, 2009b;Han et al, 2008;Lian et al, 2013Lian et al, , 2014bMatosin et al, 2013). Furthermore, rats were closely housed in a room occupied by only female rats in this study.…”
Section: Discussionmentioning
confidence: 99%